Corrosion behavior of 9Cr-1Mo steel in sulfur dioxide environment - Singh V.; Kachhawaha J.S.; Tare V.B. (My University, 2025)
Corrosion behavior of annealed 9Cr-1Mo steel was studied in SO2 environment at 1173 K, at flow rates from 8.33 × 10-7 to 33.33 × 10-7 m3/s, and parabolic rate law was followed. The rate constants were found to be independent of flow rate, within the range of flow rate investigated. Corrosion at temperatures from 973 to 1173 K, at a constant flow rate of 16.66 × 10-7 m3/s, at 1 atmospheric pressure, for 6 h also exhibited parabolic law, however, the rate constants were observed to increase significantly with rise in temperature. The outer layer of the scale formed at 973 K was essentially of iron oxide, with small amount of chromium oxide whereas the inner layer was predominantly of chromium sulphide and chromium oxide. The scale formed at 1173 K was multilayered, in contrast to double layered formed at 973 K and 1073 K. The outer thick layer of the scale formed at 1173 K, consisted of iron oxide followed by thin substrate of chromium sulphide, iron sulphide/iron oxide, and chromium sulphide/chromium oxide toward the substrate. A model is proposed for the process of corrosion of 9Cr-1Mo steel in SO2 environment, based on the present investigation. © 2014 ASM International.